A novel Fish Protein Hydrolysate supplement enhances honey bee foraging activity and colony strength: A pilot study - Hatem Sharaf El-Din; Hossam Radawan; Hamed A. Ghramh; Yahya Al Naggar (PLoS ONE, 2025)
Honey bees require diverse nectar and pollen sources for optimal nutrition, especially during late winter and early spring. This study evaluated the effect of a tuna fish protein hydrolysate (FPH)-based dietary supplement on honey bee colonies during winter season. FPH was extracted with Spasmodigestin® tablets, which increased protein content and the availability of 15 amino acids. Colonies were fed 2% FPH extract in sugar syrup (50% W/V) weekly for six weeks, while control colonies received only sugar syrup. The size of brood, honey, and bee bread areas were measured every two weeks, while foraging activity (number of incoming and outgoing foragers) was evaluated weekly. FPH-fed colonies showed improved foraging activity (130 ± 10.65%), larger brood areas (116 ± 11.10%), and higher reserves of honey (152 ± 61.87%) and bee bread (132 ± 61.39%). These findings highlight the potential of tuna FPH-based supplements to strengthen honey bee colonies during periods of limited forage availability.